Assessing the environmental impact associated with disruptive surgical bleeding - Mesut Kocaman; Stephen Johnston; Mosadoluwa Afolabi; Walter Danker; Fiona Adshead (Surgery Open Science)
Background: Minimizing avoidable healthcare resource use can support a move towards more sustainable healthcare systems. Few studies have sought to evaluate the environmental impact of complications associated with specific surgical procedures. The aim of this study was to assess the environmental impact associated with disruptive surgical bleeding across a broad range of procedures. Methods: The environmental impact assessment was performed using clinical and healthcare resource use data from a retrospective database analysis of patients with disruptive bleeding across nine procedures. Emissions data from the Sustainable Healthcare Coalition were sourced for the relevant resource use activities and used to calculate the climate, water and waste impact associated with disruptive surgical bleeding. Results: Across the procedures of interest, surgical bleeding was shown to incur a mean environmental impact of 167 kg CO2e, 267 m3 water use and 20 kg waste. Considering the incidence of disruptive bleeding per 1000 procedures, treatment of bleeding during valve procedures was associated with the highest environmental impact due to the high proportion of patients in which this complication occurs (44 %). Achieving effective and timely control of surgical bleeding events and reducing their incidence by 50 % could save up to 49 tons of CO₂e, 77,082 m3 of water use, and 6.3 tons of waste per 1000 surgical procedures. Conclusions: Surgical bleeding is associated with a substantial environmental impact. This study demonstrates the potential to use existing resource use data associated with specific healthcare activities to assess their environmental impact, helping to identify key areas for improvement in the sustainability of surgical departments.